PROBLEM EPISTEMOLOGY CHATGPT: WORLDVIEW ISLAM PERSPECTIVE SYED MUHAMMAD NAQUIB AL-ATTAS - Bramantyo Suryo Nugroho; Muchammad Taufiq Affandi; Imron Rosyadi; Isman; Muthoifin (Profetika: Jurnal Studi Islam, 2023)
This study discusses a comparison between the Islamic worldview, which emphasizes religious authority and intuition as sources of knowledge, and the contemporary worldview which focuses more on rationalism and empiricism. From the Islamic perspective, the tradition of "Khabar shadiq" derived from revelation and religious authority is the foundation of science, in contrast to the Western view which relies more on scientific methods and various sources of data, including big data. Modern technologies such as ChatGPT, which leverages big data, raise ethical and epistemological questions in the Islamization of science. ChatGPT itself faces limitations in its knowledge, while big data often faces problems of inaccuracy and bias. This research uses qualitative methods whose data sources come from books, theses, and journals on the epistemological thought of Syed Muhammad Naquib Al-Attas and the development of ChatGPT in the latest context. Using documentation data collection methods, this study highlights the importance of considering epistemological and ethical issues in the use of modern technology, to ensure a positive contribution to the advancement of Islamic civilization, while maintaining the integrity of values from an Islamic perspective.